Analyzing Augmented Reality with Problem-Based Learning to Enhance Preschoolers’ Motivation at TK Masyitoh Bangkalan - Nipan, Nipan; Bachri, Bachtiar Sjaiful; Susarno, Lamijan Hadi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study explores the integration of Augmented Reality (AR) and Problem-Based Learning (PBL) to enhance learning motivation among preschool-aged children. Using a Systematic Literature Review (SLR) guided by PRISMA standards, 9 empirical studies published between 2013 and 2023 were analyzed to examine the pedagogical impact of AR-PBL in early childhood education. The results reveal that AR increases sensory engagement and curiosity, while PBL encourages critical thinking, collaboration, and autonomy. Together, AR-PBL fosters deeper exploration, sustained attention, and task persistence in learners aged 4–7. Despite its benefits, implementation challenges persist, including lack of teacher training, limited infrastructure, and the need for culturally relevant content. The study highlights the potential of AR-PBL to transform traditional instruction, particularly in under-resourced rural settings like TK Masyitoh Bangkalan, where themes such as “recognizing nearby animals” can be enhanced through immersive, localized learning experiences. This review concludes that AR-PBL represents a promising educational innovation aligned with developmentally appropriate practices. Future research should focus on classroom-based trials and long-term impact studies. The findings provide practical recommendations for educators and developers to design engaging, accessible, and context-sensitive digital learning environments for early childhood learners.